2020
DOI: 10.1111/all.14350
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children aged 8‐12 years undergoing food allergy oral immunotherapy: Child and parent perspective

Abstract: Background: Oral immunotherapy (OIT) for food allergy improves the quality of life (QOL) of children from parental perspective but little is known about the child perception. Methods: The Food Allergy Quality of Life Questionnaire-Child Form (FAQLQ-CF) was administered to children aged 8-12 years, and the FAQLQ-Parent Form (FAQLQ-PF) was administered to their parents at the start of OIT for milk, egg, peanut, sesame, or tree nuts, at the end of up-dosing, and after 6 months of follow-up. Food-allergic children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 50 publications
(132 reference statements)
3
40
1
1
Order By: Relevance
“…The risk–benefit ratio of OIT is still debated. While the efficacy of this approach has been well studied, the evaluation of an effective improvement in the QoL of the patient remains limited to small or uncontrolled studies [ 139 ]. In fact, only few studies evaluate children’s perceptions of improved of their QoL as compared to perceptions by parents.…”
Section: Treatment and Oral Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The risk–benefit ratio of OIT is still debated. While the efficacy of this approach has been well studied, the evaluation of an effective improvement in the QoL of the patient remains limited to small or uncontrolled studies [ 139 ]. In fact, only few studies evaluate children’s perceptions of improved of their QoL as compared to perceptions by parents.…”
Section: Treatment and Oral Immunotherapymentioning
confidence: 99%
“…In fact, only few studies evaluate children’s perceptions of improved of their QoL as compared to perceptions by parents. A recent paper [ 139 ] described how OIT could improve the QoL of (both partially and totally desensitized) food-allergic children and their parents, through the Food Allergy Quality of Life Questionnaire—Child Form (FAQLQ-CF) and the FAQLQ—Parent Form (FAQLQ-PF), respectively. These results were concordant with those of Carraro et al, who gave the same questionnaire to parents of patients with CMA and found a substantial increase in all the investigated areas of QoL (emotional impact, food anxiety, and social and dietary limitations) in children with CMA [ 140 ].…”
Section: Treatment and Oral Immunotherapymentioning
confidence: 99%
“…Three studies that used the validated Food Allergy Quality of Life Questionnaire and included controls reported improvement in scores pre-and postactive OIT in children and/or their parents. 11,24,25 Further study into the effect of OIT on QOL will facilitate the discussion of long-term benefits of this treatment.…”
Section: Net Health Benefit Of Oitmentioning
confidence: 99%
“…13 Proactively protecting children from accidental ingestions that are mostly inevitable can be life-changing, and it is evident to providers of OIT that most patients on such therapies and their families experience gratitude and relief. 11,25 Patient advocacy groups, such as Food Allergy Research and Education, invested start-up funds into new companies that would be able to translate emerging data from small clinical trials done at academic centers into phase II and III clinical studies that could lead to an FDA-approved product for clinical use. On its website, Aimmune Therapeutics credits its formation ''to a united call to action by leading stakeholders in food allergy.''…”
Section: Net Health Benefit Of Oitmentioning
confidence: 99%
See 1 more Smart Citation